The Other Election Controversy of Y2K: Core First Amendment Values and High-Tech Political Coalitions - Marc John Randazza (Washington University Law Quarterly, 2004)
As the 2000 campaign reached its climax, some renegade supporters of Green Party candidate Ralph Nader countered critics’ charges that they were “handing the election to Bush” by creating websites encouraging vote-swapping. The theory of this practice was: A Nader supporter in a hotly contested state would agree to vote for Al Gore if a Gore supporter in an uncontested state would vote for Ralph Nader. The object was to help deliver five percent of the popular vote to the Green Party (so that the Greens would receive federal matching funds for the 2004 presidential election) while simultaneously working to prevent a George W. Bush presidency. With the election less than a week away, and the poll margins closer than any election in recent history, several state election officials acted to snuff out the online vote-swapping movement by threatening vote-swap site operators with fines and/or imprisonment. The chilling effect brought about by the letters from state regulators may have tipped the scales in the 2000 campaign, even though no one knew whether prohibiting vote-swapping was constitutional. This study introduces the reader to the concept and practice of vote-swapping. It examines the chilling effect of the threats of prosecution issued during the 2000 election and these effects’ possible electoral consequences. This study analyzes online vote-swapping under various state laws and state constitutions and extends the analysis to encompass federal election law and federal constitutional law. Finally, this study examines the ethics of vote-swapping and concludes that the practice is legal under most state election laws, protected under most state constitutions, protected by the federal Constitution, and an ethical use of personal voting power.
Keywords: Elections; Internet; Freedom of speech; Freedom of association; Campaign funds; Internet voting; Political movements